Conceptual design of 5 kW PEM fuel cell stack - Siti Kartom Kamaruddin; Wan Ramli Wan Daud; Ayub Md. Som; Mohd. Shahbudin Masdar (2007)
The main objective of this paper is to conceptually design the stack of Proton Electrolyte Membrane (PEM) fuel cell taking into consideration the voltage for a single cell, number of cells required, current density, power density and ﬁnally the current ﬂow in the stack. A part from that, effect of important parameters such as temperature, pressure, voltage, current density and distance gas ﬂow channel were presented in this paper. From the result, it was observed that 32 numbers of cells (0.7 V for each single cell) with a current ﬂow of 260A were required for power output of 5 kW after considering the parasitic load of 8% from the total power output. The active area of the single cell was found to be about 250 cm2. The current density and power density were determined as 900 mA/cm2 and 660 mW/cm2, respectively. The cell efﬁciency is expected about 65%. Finally, the electricity cost in this study was calculated as RM 0.152/ kWh-1